Farmers’ Willingness to Continue on Rice High-Yileding Varieties in South Sulawesi Province: The Influence of Attitudes towards Variety Attributes and Socioeconomic Aspects - Fahmi, Diah Arina; Irham, Irham; Waluyati, Lestari Rahayu (Perum BULOG, 2023)
High-yielding varieties are technological innovations readily accepted by farmers and proven to increase rice productivity. This study aimed to determine the attitude of farmers toward the attributes of rice varieties and compare their willingness to continue in rice varieties and identify influencing factors. This research was conducted from December 2020 to January 2021 with 101 farmers, selected by purposive sampling, using Ciherang and Inpari 37 varieties in South Sulawesi. Farmers’ attitudes towards the attributes of rice varieties were measured by Fishbein analysis. Proportion analysis was done to determine farmers’ willingness to continue using the Ciherang and Inpari 37 varieties, and binomial logistic analysis was used to estimate the factors that influence it. The results showed that farmers’ attitudes toward the attributes of the Ciherang variety were mainly higher than that of Inpari 37, except for attribute productivity, pest and disease resistance, milled yield quality, and grain selling price. The level of willingness of farmers to continue using Ciherang and Inpari 37 was in the high category with a higher Ciherang value than farmers of Inpari 37. The factors influencing the willingness to continue for both varieties were rice texture, resistance to pests and diseases and the selling price. Other factors variably influenced the willingness of farmers to continue for both varieties.